Effects on the Potential for Seepage Failure Under a Geotextile Mattress with Floating Plate - Yehui Zhu; Qiyun Wang; Guokai Wu; Yanhong Li; Liquan Xie (Journal of Marine Science and Engineering)
The geotextile mattress with floating plate (GMFP) is an innovative scour protection device. This study examines the potential for seepage failure under the GMFP, which has been previously documented. The effects of flow velocity and GMFP configuration on the potential for seepage failure were analyzed. The variation pattern of the sloping angle was first revealed in flume tests, and the bed pressure near the GMFP with various configurations in steady currents was thereafter simulated. The average hydraulic gradient across the GMFP was observed to increase with an increase in the Froude number before reaching a plateau, which can be explained by the coupled effects of the rising Froude number and the decreasing sloping angle. The average hydraulic gradient was approximately inversely proportional to the mattress length upstream of the floating plate. With the decreasing mattress length downstream of the floating plate, the average hydraulic gradient initially rose and then declined when the downstream mattress was relatively short. This trend can be associated with the amplification of the vortices in the top vortex zone downstream of the GMFP with the shortened downstream mattress, which pushed the bottom vortex to the leeside. The shortened downstream mattress could increase the risk of overturning and slipping of the GMFP, although the average hydraulic gradient decreased.